Aquatic physical activities and physical self-concept in students of sports science - Humanchumo Barrientos, Vanessa (2019)
The objective of the research was to determine the relationship between the variables physical self concept and aquatic activities in the students of the second and third cycles of a professional school of sports science at a private university in Lima. The descriptive correlational design was used. The study was carried out under the quantitative approach. The population consisted of 521 students enrolled in the different cycles, of which a total of 53 attending students was selected as a sample. For data collection, a validated instrument was used to measure physical self-concept: the CAF questionnaire, field cards, and a targeted survey. It was concluded that there is a significant association between the variables physical self-concept and aquatic activities according to the Spearman's Rho statistic, obtaining a value of, 501; Furthermore, the degree of existing linear association was 50.1%, which is why it was determined that there was a significant association between physical abilities and aquatic physical activities.